2008
DOI: 10.1146/annurev.neuro.31.061307.090711
|View full text |Cite
|
Sign up to set email alerts
|

Role of Axonal Transport in Neurodegenerative Diseases

Abstract: Many major human neurodegenerative diseases, including Alzheimer's disease, Parkinson's disease, and amyotrophic lateral sclerosis (ALS), display axonal pathologies including abnormal accumulations of proteins and organelles. Such pathologies highlight damage to the axon as part of the pathogenic process and, in particular, damage to transport of cargoes through axons. Indeed, we now know that disruption of axonal transport is an early and perhaps causative event in many of these diseases. Here, we review the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
478
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 656 publications
(492 citation statements)
references
References 147 publications
(175 reference statements)
8
478
0
6
Order By: Relevance
“…Perturbations of microtubule-based transport are implicated in an increasing number of neurodegenerative diseases (NDs) (37). FEZ1 not only transports Stx but also synaptic vesicles (3) and mitochondria (38).…”
Section: Discussionmentioning
confidence: 99%
“…Perturbations of microtubule-based transport are implicated in an increasing number of neurodegenerative diseases (NDs) (37). FEZ1 not only transports Stx but also synaptic vesicles (3) and mitochondria (38).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, it has been shown that mutations in transport-related genes can result in neurodegenerative phenotypes in mice and humans (3,4). Because transport deficits have been reported in many neurodegenerative diseases, including Alzheimer's disease, Huntington's disease, and amyotrophic lateral sclerosis (ALS) (5)(6)(7)(8), it is commonly assumed that disturbances in axonal transport are key pathological events that contribute to neurodegeneration (9)(10)(11). However, the causal relationship of axonal transport disturbances to degeneration remains unclear.…”
mentioning
confidence: 93%
“…Several types of vesicles, including amyloid precursor protein (APP) vesicles, depend upon kinesin-1 (9, 13-17) for their anterograde movement in axons. These studies raised the possibility that APP transport and its influence on APP proteolytic processing play an important role in the development of Alzheimer's disease (1,3,9,(18)(19)(20).Although much progress has been made toward elucidating underlying principles of motor coordination (21-25), we lack a full understanding of how motor subunits are recruited to APP vesicles and, moreover, how levels of these subunits on vesicles are determined. Previous work raised the possibility that APP could bind to KLC and thus kinesin-1 either directly or indirectly via complex formation with JIP1 (9, 26, 27), a proposal that has remained controversial in the field.…”
mentioning
confidence: 99%
“…These motor proteins and their regulators play critical roles in long-distance signaling events in neurons, neuronal regeneration, and in the development of neurodegenerative disease (1)(2)(3). Several diseases in humans, such as hereditary spastic paraplegia (4), CharcotMarie-Tooth type 2 (5), and ALS-like motor degeneration (6), have been linked directly to mutations in genes encoding motor proteins.…”
mentioning
confidence: 99%